1977
DOI: 10.1002/jmv.1890010303
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological investigation of patients and family contacts in an epidemic of hepatitis A

Abstract: Serial blood and faecal samples were collected from patients and family contacts during an outbreak of hepatitis A in a village and tested by a solid-phase competitive type radioimmunoassay for hepatitis A antigen and hepatitis A antibody. The amount and duration of excretion of hepatitis A antigen was correlated with the severity of the illness. In 2 severe clinical cases, hepatitis A antigen was demonstrated in faecal extracts 11 days before the onset of jaundice and continuing for 10 days thereafter, with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1978
1978
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] In neonates, fecal excretion of HAV RNA may continue for as long as 6 Sensitivity of RT-PCR. Substances normally found in stool can inhibit the PCR reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] In neonates, fecal excretion of HAV RNA may continue for as long as 6 Sensitivity of RT-PCR. Substances normally found in stool can inhibit the PCR reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were either of malignant origin [Frosner et al, 1979;Locarnini et al, 1981;Deinhardt et al, 19811, and some of them contained the hepatitis B virus genome [Frosner et al, 1979;Deinhardt et al, 19811, or were available in only limited quantities [Provost and Hilleman, 1979;Flehmig, 19801, thus preventing the production of larger amounts of HAV for use in research and preparation of antigens for diagnostic tests or vaccine development. Therefore, we tested other cell types, including human diploid fibroblasts, for susceptibility to infection with HAV.…”
Section: Discussionmentioning
confidence: 99%
“…After inoculation of PLC/PRF/5 cells with HAV-containing human stool, hepatitis A antigen (HAAg) appeared only after more than 7 weeks of incubation, and the infectivity titer in tissue culture reached about 100-1,000 [Frosner et al, 1979;Deinhardt et al, 19811 . During serial passage of the virus in tissue culture, the infectivity titer increased and the time of first appearance of HAAg shortened to 1-2 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also analyses for antibodies to the hepatitis B core antigen (anti-HBc) by immunoelectro-osmophoresis (Hansson and Johnsson, 1971) and hepatitis Be antigen (HBeAg) and its antibody by immunodiffusion (Magnius et al, 1975) were found to be negative. Analyses for antibodies against hepatitis A virus (anti-HAV) by radioimmunoassay (Frosner et al, 1977) A liver biopsy one year later revealed progression to chronic active hepatitis with signs of cirrhosis (Fig. 6) (Fig.…”
mentioning
confidence: 99%